Improving Speaking Skills through Cooperative Learning Model Talking Stick Type on Students of Class XI IPS 2 SMA Negeri 7 Singkawang School Year 2015/2016 - Dionesia Marisa Ica; Mardian Mardian; Wahyuni Oktavia (JP-BSI (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2017)
This research is motivated by low speech skills, this is due to low student interest and lack of confidence in students and has difficulty in playing the drama. This research is focused on the material to play the drama through Cooperative Type Talking Stick Learning Model. The purpose of this study is to describe the planning, implementation, and results of the Drama through Cooperative Learning Model Type Talking Stick. The formulation of this research problem is how the planning, how the implementation, and how the results of learning activities play the drama through Cooperative Type Talking Stick Learning Model. the method used in this research is descriptive with the form of qualitative and quantitative research. The implementation procedure of this research consists of planning, implementation, observation, and reflection. Research design in the form of Class Action Research. Planning in cycle 1 is good with percentage equal to 74,11% whereas planning in cycle 2 with percentage 80%. Implementation in cycle 1 first meeting is good with percentage equal to 71,81% while implementation in cycle 1 second meeting equal to 72,17%. The percentage achieved in cycle 1 overall was 74.54%. Implementation in cycle 2 first meeting Very good with percentage 85.45%, the percentage achieved in cycle 2 second meeting very good with percentage 87,27%. Percentage achieved in cycle 2 overall by 86,36%. Research Result Action Class at cycle 1 with average score reach 69,01 and percentage mastery learn student equal to 53,33%, themean value in cycle 2 increased become 71,41 with student mastery percentage equal to 83,33%. Based on this research, it can be concluded that speaking skill in playing drama through Cooperative Learning Model Talking Stick Type is good, it is suggested to teachers especially Indonesian teachers using Cooperative Learning Model Talking Stick Type improves speaking skill especially on play plays material.